Pengembangan Kelembagaan Badan Usaha Milik Desa Dalam Menggerakkan Ekonomi Desa di Provinsi Riau - MUAMMAR ALKADAFI; Syukran Tauby; Nurul Lovi Andini (UIR Press, 2021)
Village-Owned Enterprises increasingly grow and develop, especially after the enactment of Law No. 6 of 2014 concerning Villages. From the large number of Village-Owned Enterprises that have been formed, there are those who have succeeded in running their business, and there are also those that have been running in place or failing. The purpose of this study was to determine the driving factors for forming and supporting the success of Lancang Kuning Village, Amanah Sejahtera and Paris Mandiri Village Enterprises. The research method used in this research is qualitative research with a descriptive approach. Data collection techniques carried out by observation, in-depth interviews and documentation. Determination of informants is done purposively. Data were analyzed by data reduction, display / presentation of data, and drawing conclusions. As a result of the research, the institutions of Lancang Kuning Village Owned Enterprises, Amanah Sejahtera and Paris Mandiri were formed due to the intervention of the Riau Provincial Government through the Village Empowerment Program (PPD), Village Owned Enterprises received strong political and legal protection through Law Number 6 Year 2014 About the Village. The supporting factors for success are natural capital, financial resources, human resources and social capital. Besides that, it is also supported by the leadership factor of the innovative village head - progressive, the manager of the Village Owned Enterprises who have the harmony, innovative and creative, the mindset (maindset) to move forward.